Remembering Oscar Romero and the Martyrs of El Salvador A Cloud of Witnesses - John S. Thiede (Lexington Books, 2017)
With the Beatification of Monseñor Oscar Romero, our current Pope Francis has asked theologians to consider how we might allow for an expanded definition for martyrdom in the 21st century. Remembering Oscar Romero and the Martyrs of El Salvador responds to that challenge. How do we name Oscar Romero, Rutilio Grande, the U.S. churchwomen, and the Jesuits and two laywomen killed at the UCA as martyrs? Is it a new category with a new definition? Or is it simply an amplification of what we have long considered Christian witness? While there is a long history of martyrdom in Latin America, this book elaborates on four case studies for martyrdom focusing on the reality in El Salvador: Rutilio Grande, S.J. killed in 1977, Archbishop Oscar Romero killed in 1980, the U.S. churchwomen killed in 1980, and the six members of the UCA Jesuit community and their two female collaborators killed in 1989. Insights from the work of Jon Sobrino illuminate these case studies. First, his Christological insights from Jesus the Liberator and Christ the Liberator are used to analyze the reality of martyrdom, particularly in reference to the terms martyr, crucified people, and martyred people. Second, his more recent articles challenge a strict interpretation of the traditional definition of martyrdom, especially focusing on his terms Jesuanic martyr, a martyr for justice, and even a more polemic suggestion of an anonymous Christian martyr. Finally, the book concludes by combining Sobrino's insights and the reality of martyrdom today, updated with the recent scholarship in Romero's beatification process which attempts to show Romero as a martyr. In the end, the book hopes to offer some suggestions for an expanded definition of martyrdom in the 21st century. By responding to the call of Pope Francis for an expanded definition, the reality of martyrdom in Latin America might be better understood and applied to the universal church.